Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.4028/www.scientific.net/msf.696.200
|View full text |Cite
|
Sign up to set email alerts
|

Water Vapour Effects on the Oxidation of Chromia-Forming Alloys

Abstract: The electronic properties of chromia scales grown between 800°C and 900°C on chromium metal and chromia-forming ferritic stainless steels were determined using room temperature PhotoElectroChemistry (PEC) experiments and the relative importance of the n- and p-character of the scales could be assessed. According to the thermodynamic previsions of defects structures, the external part of all the scales grown in oxygen exhibits band gap energy around 3.5 eV, with a marked p-type character on chromium and a possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…1). Being more uniform and homogeneous, the H 2 -H 2 O grown chromia scales additionally demonstrate a better adherence to the metal [40,44] and show no signs of delamination over GBs. However, smooth oxide bulges are visible over the GBs accompanied by abundant porosity in the alloy subsurface.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…1). Being more uniform and homogeneous, the H 2 -H 2 O grown chromia scales additionally demonstrate a better adherence to the metal [40,44] and show no signs of delamination over GBs. However, smooth oxide bulges are visible over the GBs accompanied by abundant porosity in the alloy subsurface.…”
Section: Resultsmentioning
confidence: 96%
“…To check the influence of the chromia scaling mechanism, i.e., oxide growth direction, on intergranular corrosion, the exposures in a flow of Ar-5 H 2 %− 3%H 2 O were performed in a closed, gas-tight quartz tube. It is well known that water vapor promotes inward growth of Cr 2 O 3 and this inwardly grown chromia usually grows faster and adheres better to metal [35,39,40]. The Ar-5%H 2 gas mixture supplied by Linde gas (AGA AB, Lidingö, Sweden) was bubbled through a humidification setup held at 24.4 • C to obtain 3% absolute humidity (30 mbar of H 2 O).…”
Section: Exposuresmentioning
confidence: 99%
“…For thermally grown chromia on chromium and stainless steels, the photoelectrochemistry measurement showed that the semiconducting type of the oxide turned from amphoteric p+n when oxidised in oxygen into n when oxidised in water vapour [37,39]. This effect is less for stainless steel since the iron doping into the oxide might weaken its p-type property [37,39].…”
Section: Defect Structural Analysis Whenmentioning
confidence: 99%
“…For thermally grown chromia on chromium and stainless steels, the photoelectrochemistry measurement showed that the semiconducting type of the oxide turned from amphoteric p+n when oxidised in oxygen into n when oxidised in water vapour [37,39]. This effect is less for stainless steel since the iron doping into the oxide might weaken its p-type property [37,39]. From these results, we may consider that, for the oxidation of chromium or the chromia-forming stainless steel in water vapour, the hydroxyl ion might be incorporated into the oxide in the substitutional site and diffuses via the oxygen vacancy, or it might be incorporated into the oxide grain boundary and further diffuses to the metal/scale interface.…”
Section: Defect Structural Analysis Whenmentioning
confidence: 99%
See 1 more Smart Citation